Dhupana With Nimbapatra As A Adjuvant Therapy To Manage Vrana- A Review. - Sharma, Divyadeepak; Rahul; Rathore, Abhinav; Sharma, Nitika (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda since the very start has always emphasized upon a healthy living in order to maintain the health of an individual. But if at all an individual suffers a disease in order to overcome its bad prognosis ayurveda has also mentioned about time tested remedies and procedures which when done can yield marvelous and miraculous results. Sir Joseph lister had quoted that “skin is the best dressing” but what if it somehow gets distorted, disrupted or broken may be of any random injury, wound or perhaps an abcess.So, here we will discuss about the adjuvant therapy of dhupana karma stated under “vrana Shashtyopkrama” in the 1stchapter of Sushruta Samhita Chikitsa sthana which is named as “Dwivarniye Adhyaya ” as one of the raksha karma in the management of vrana(wound). For the procedure of Dhupana karma here, the drug discussed is dried nimba patrachurna. The idea behind choosing nimbi patra is discussed below in the paper.